PENGARUH TAX EXPENSES, TAX HAVEN UTILIZATION, FOREIGN OWNERSHIP DAN INTANGIBLE ASSETS TERHADAP TRANSFER PRICING - Wulandari, Enthy Sulistya Suci; Irawati, Wiwit (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research aims to examine the influence of tax expenses, tax haven utilization, foreign ownership and intangible assets on transfer pricing. The population in this study are energy sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method uses a purposive sampling method, with several predetermined criteria, there are 7 companies with observations for 5 years in quarterly reports, so the total sample is 140 data. The data analysis technique used is multiple linear regression analysis technique with eviews 12 program. The results of the regression test in this research prove that in particular, tax haven utilization and intangible assets have a negative effect on transfer pricing, while tax expenses and foreign ownership have no effect on transfer pricing. Tax burden is no longer a determining factor in a company's transfer pricing transactions, because there is a regulation from the government that requires the use of fair market value in transactions with affiliated parties/parties with special relationships. The amount of tax burden paid by the company cannot guarantee the company to transfer pricing, or it can also be caused by the stricter supervision of tax officers against the company.